Post-traumatic stress and related symptoms in a gestation after a gestational loss: narrative review - Fernández-Ordóñez, Eloísa; Rengel-Díaz, Cristóbal; Morales-Gil, Isabel María; Labajos-Manzanares, María Teresa (Instituto Nacional de Psiquiatría Ramón de la Fuente Muñiz, 2018)
Background. Around 30% of pregnancies conclude in a gestational loss. Most women who suffer a gestational loss become pregnant again. However, mothers who have experienced this situation live the new pregnancy with fear and anxiety. Objective. To perform an update of the main works done in the study of post-traumatic stress and related symptoms during pregnancy after a gestational loss. Method. The Medline database was consulted. Articles published from 2007 to date were selected. Key words related to the topic of study were used. Results. The studies reviewed showed five entities that deserve attention during a pregnancy achieved after a gestational loss: post-traumatic stress, depression, anxiety, relationship, and relationship with the future child. There is a relationship between the presence of post-traumatic stress and the risk of developing depression and anxiety. Discussion and conclusion. Women who experience perinatal loss, regardless of the type of loss and the gestational age in which it occurs, are at risk of continuing grief, symptoms of depression, anxiety, and post-traumatic stress in later pregnancy. The gestational age and the time elapsed between the perinatal loss and the next pregnancy seem to be the most influential factors in the development of post-traumatic stress sindrome, and symptoms of dysfunctional grief, anxiety, and depression.
Keywords: Salud mental; Mental health; Perinatal loss